Analysis of Difficulties in Understanding Calculus Concepts: A Case of Teachers and Students - Harahap, Minarni Ikhrimah; Herianto, Ramadhan; Siregar, Rama Nida (IKIP Siliwangi, 2025)
Calculus is a fundamental component of secondary mathematics education; however, students’ conceptual understanding remains limited, particularly in abstract topics such as derivatives and integrals. These challenges are further exacerbated by low engagement and ineffective instructional practices. This study aims to analyze students’ difficulties in learning calculus, identify factors influencing their learning interest, and examine teachers’ instructional challenges. This study employed a descriptive qualitative approach involving 12 participants, consisting of 10 Grade XII students and 2 mathematics teachers at MAN 2 Padangsidimpuan. Data were collected through semi-structured interviews, classroom observations, and documentation of students’ written work. The researcher acted as the primary instrument, supported by interview guidelines and documentation sheets. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. To ensure trustworthiness, source and technique triangulation were applied. The findings indicate that students exhibit a moderate level of learning interest (≈54.6%), yet experience significant difficulties in conceptual understanding and mathematical communication, particularly in trigonometric derivatives and integrals. These difficulties are primarily associated with weak prerequisite knowledge, reliance on procedural memorization, and limited use of visual learning media. Additionally, teacher-centered instruction and anxiety-inducing assessment practices contribute to low student engagement. In conclusion, calculus learning difficulties are multidimensional, involving cognitive, affective, and instructional factors. Therefore, a holistic instructional approach integrating conceptual understanding, interactive media, and student-centered strategies is essential to improve learning outcomes.